(untitled) (Journal of Computational Mathematics, 2002)
In this paper, we first give a smoothing approximation function of nonsmooth system based on box constrained variational inequalities and then present a new smoothing approximation algorithm. Under suitable conditions, we show that the method is globally and superlinearly convergent. A few numerical results are also reported in the paper.